Transformation of International Criminal Justice Principle into Indonesia National Criminal Justice System: How Domestic Law Adopt Global Values? - Amandha, Asyaffa Ridzqi; Arifin, Ridwan (International Law Discourse in Southeast Asia, 2024)
Indonesia is one of the countries that adhere to a legal system in it. As a rule of law, of course, it has become a natural thing when all the activities and activities of each individual and the state have been regulated under the rule of law. To create law, specifically a better criminal law. So it is necessary for law enforcement, the rule of law, the legal process, and all aspects of the law to be better. All of these aspects have been regulated in the criminal justice system. The criminal justice system requires synchronization, where the contents of this synchronization will regulate aspects of substance, structural aspects, and cultural aspects in it. Where all of these aspects must be able to synchronize with each other to integrate with a substantial aspect. The role of international criminal law as one of the guidelines in the national criminal justice system is very closely related. The author wants to examine what is the National and International Criminal Justice Systems? and What is the relationship between the Indonesian criminal justice system and international criminal law?International Criminal Law; National; Criminal Justice System.